2020
DOI: 10.1186/s13019-020-01198-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of postoperative complication and prolonged intensive care unit stay after complete pericardiectomy in tuberculous constrictive pericarditis

Abstract: Background: The risk factors of postoperative outcomes after pericardiectomy in tuberculous constrictive pericarditis have still been unclear. This study aimed to investigate the predictors of postoperative complication and prolonged intensive care unit (ICU) stay in the patients with tuberculous constrictive pericarditis undergoing pericardiectomy. Methods: A total of 88 patients with tuberculous constrictive pericarditis undergoing pericardiectomy were retrospectively enrolled. Logistic regression and Cox re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Other factors that may predict poor long-term survival include higher pulmonary artery systemic pressure, abnormal LV systolic function, lower sodium level, and older age. Factors such as pre-operative NYHA functional class, pre-operative RV dilatation, pre-operative central venous pressure, and reduced LV systolic function are predictors of early post-operative and 30-day mortality [ 71 , 72 ].…”
Section: Role Of Multimodality Imaging In Pre-operative Planning and ...mentioning
confidence: 99%
“…Other factors that may predict poor long-term survival include higher pulmonary artery systemic pressure, abnormal LV systolic function, lower sodium level, and older age. Factors such as pre-operative NYHA functional class, pre-operative RV dilatation, pre-operative central venous pressure, and reduced LV systolic function are predictors of early post-operative and 30-day mortality [ 71 , 72 ].…”
Section: Role Of Multimodality Imaging In Pre-operative Planning and ...mentioning
confidence: 99%
“…Despite being considered effective, pericardiectomy is associated with non-negligible risk of postoperative complications and in-hospital mortality. There have been a number of studies exploring the risk factors of poor outcomes after pericardiectomy, and the results showed that surgical outcomes depended heavily on the functional status of patients, the etiology of constrictive pericarditis, the timing of surgical intervention, the extent of pericardial resection and the need for cardiopulmonary bypass [16][17][18][19][20]. However, most of the studies represented single-center and retrospective experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported the negative impact of renal dysfunction on patient outcomes and medical costs in pericardiectomy (4,5,16,17), but the predictors of renal dysfunction have hardly been investigated. Huang et al studied the clinical features of ninety-two patients with constrictive pericarditis, and reported that ventilator time, postoperative creatinine levels and blood transfusion were associated with acute kidney injury after pericardiectomy, with no preoperative factors involved.…”
Section: Discussionmentioning
confidence: 99%